HEALTHINESS LITERACY: THE LOST VACCINE IN PAKISTAN’S CONTEST AGAINST ILLNESS. : https://doi.org/10.46536/jpumhs/2025/15.03.650 - PROF ANWAR ALI JAMALI , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2025)
Pakistan has eliminated smallpox, nearly abolished polio, & moved out COVID-19 vaccines to lots—but still we remain unprotected contrary to a far lethal pathogen: unawareness. Little healthiness knowledge is the quiet collaborator in motherly expiries, vaccine denial, quackery, and then the fast spread of avoidable illnesses.